The degree of taking into account the questions of the physics book for the twelfth grade for the scientific and industrial branches in Jordan, according to Bloom's modified levels of knowledge - Al- shurfat, Mashor Saker Mfadi (Journal of Educational and Psychological Sciences, 2020)
This study aimed to analyze the questions of physics book for the twelfth grade for science and industry branch in Jordan in light of bloom’s revised taxonomy. Which consisted of (94) major questions, includes (261) sub-questions, where the sub-question was considered a unit of analysis. The researcher adopted the intentional method in selecting the sample and used the descriptive analytical approach to conduct the study, where he used a card to analyze the levels of cognitive levels according to the Bloom’s taxonomy. The searcher used percentages and the arithmetic mean of the statistical treatment, the results showed that the physics book questions focused on two dimensions of the knowledge (factual knowledge (25%) & conceptual knowledge (75%)). but in the cognitive process dimensions focused on the lowest thinking levels (25- 43 %), where the level of (apply) came in the first place (43%), and (remember)in the second (30%), and (understand)in the third (25%). While it showed weakness in the focus on the higher thinking levels, the level of (analyze) got (2%), and there were no levels of evaluating and creating levels. The study recommended that the questions should be distributed over all of the knowledge dimensions, especially (procedural knowledge & creative knowledge), also should focus on the higher thinking levels, and trains the authors of the questions in preparing and formulating the questions in a manner consistent with cognitive levels of Bloom's revised classification.
Keywords: Bloom's taxonomy; physics; twelfth grade; Jordan